222k views
0 votes
The answer is 48 can someone explain how?

The answer is 48 can someone explain how?-example-1

1 Answer

2 votes

Answer:

48

Explanation:

(1)

apple × apple × 2apple = 54

2apple³ = 54 divide both sides by 2

apple³ = 27 → apple = ∛27

apple = 3

(2)

apple + apple × green_apple = 24 substituite apple = 3

3 + 3 × green_apple = 24 subtract 3 from both sides

3 × green_apple = 21 divide both sides by 3

green_apple = 7

(3)

strawberry - bannana - banana = 0 → strawberry = 2banana

(4)

strawberry + banana + cherry = 24 substitute from (3)

2banana + banana + cherry = 24

3banana + cherry = 24

(5)

apple + banana - cherry = -1 substitute apple = 3

3 + banana - cherry = -1 subtr3 from both sides

banana - cherry = -4

Add both sides of (4) and (5)

3banana + cherry = 24

+banana - cherry = -4

4banana = 20 divide both sides by 4

banana = 5

Substitute it to (4):

3(5) + cherry = 24

15 + cherry = 24 subtract 15 from both sides

cherry = 9

Substitute to the last equation:

3 + 5 × 9 = 3 + 45 = 48

/USED PEMDAS/

User Esengineer
by
4.6k points